An Evaluation of Natural Environment Interventions for Informal Cancer Caregivers in the Community - Rebecca H. Lehto (MDPI AG, 2021)
Home-based informal caregiving by friends and family members of patients with cancer is be-coming increasingly common globally with rates continuing to rise. Such caregiving is often emo-tionally and cognitively demanding, resulting in mental exhaustion and high perceived burden. Support for caregivers may be fostered by engagement with the natural environment. Interaction with nature is associated with mental health benefits such as stress reduction and improved well-being. The purpose of this paper was to evaluate the state of the science regarding the use of nat-ural environment interventions to support caregivers of cancer patients in the community. A comprehensive scoping review using the Arksey and O’Malley framework and the Preferred Re-porting Items for Systematic Reviews and Meta-analyses assessed natural environment therapies and mental health outcomes among cancer caregivers. Databases searched included CINAHL, PubMed, Scopus, Cochrane, and Alt HealthWatch. Findings recovered a total of five studies over a 10-year period that met criteria, demonstrating a lack of empirical evidence addressing this po-tential resource to support caregivers. Often, study appraisal was not on nature exposure, but ra-ther other aspects of the projects such as program evaluation, exercise, or complementary thera-pies. Both qualitative and quantitative designs were used but sample sizes were small. Caregivers experienced beneficial results across the various studies and future work could enhance these findings.